Shifting Journalistic Values of Cyber Media in the Social Media Era - Muslikhin Muslikhin; Deddy Mulyana; Dadang Rahmat Hidayat; Prahastiwi Utari (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2026)
The presence of social media has transformed the journalistic workflow in Indonesia, from planning, production, to news distribution. This research aims to uncover the dynamics of shifting journalistic values in the working practices of Indonesian cyber media as they interact with social media, through a case study of Tribunnews.com. The research uses a qualitative approach with a constructivist paradigm and a descriptive qualitative method.  The theoretical framework used is market-driven journalism, professional-driven journalism, and the theory of social responsibility media. Data were collected through semi-structured interviews with 13 informants from various editorial levels to obtain a comprehensive understanding of journalistic practices in the newsroom. Data analysis was conducted using Creswell's qualitative analysis stages. The research results show that social media encourages tension between market orientation and professional values in journalistic practice. On one hand, virality, trending topics, and traffic potential increasingly influence the determination of news value and coverage priorities. On the other hand, Tribunnews.com strengthens various professional mechanisms to maintain journalistic quality, such as enhancing verification standards, developing fact-checking units, implementing stricter editorial oversight, and respecting intellectual property rights. These findings indicate that the shift in journalistic values is not a replacement of professional values by market logic, but rather an ongoing negotiation between algorithmic demands, audience interests, and social media responsibilities within the digital ecosystem.